PENGARUH LDR, CAR, DAN ROA TERHADAP TINGKAT SUKU BUNGA DEPOSITO BERJANGKA (Students' Journal of Accounting and Banking, 2013)
This research aims to analyze the influence of the Loan to Deposit Ratio (LDR), Capital Adequancy Ratio (CAR), and Return On Assets (ROA) influence on interest rate term deposit At banking company registered in BEI. The population in this research is on the banking company financial reports published by BEI Indonesia during the period 2008-2010. As for the technique of collecting samples in this study by using purposive sampling method that samples taken on the basis of criteria used by the researchers. Samples taken, as many as 10 commercial banks in 2008-2010. Test the hypothesis in this study using multiple linear regression analysis. The results of this research are the coefficients of LDR and CAR shows positive direction, so that will increase the determination of the interest rates of deposits, and showing a negative direction coefficient ROA means rise in ROA will decrease the determination of deposit rates. From this research it can be concluded that based on the results of statistical tests that variable positive effect significantly to LDR determination of deposit rates, variable CAR did not affect significantly to the determination of deposit rates and variable is negative andsignificant influential ROA against the determination of deposit rates.Keywords: Pengaruh LDR, CAR dan ROA terhadap tingkat suku bunga deposito berjangka